Measuring France Hegemony in the European Space Agency (ESA) - Meirizal, Ade; Syahfa, Muhammad Rayhan Faqih (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2024)
Control over resources, actors, and events and outcomes are three of many approaches offered by International Relations studies in terms of measuring power. This paper highlights the crucial role of power measurement in astropolitics, based on the context of the European Union (EU). In particular, it focuses on France's hegemony in the European Space Agency (ESA) using the Hegemonic Stability Theory (HST) to observe the structural power within the ESA. To analyze this, the author uses the regime concept and the theory of hegemonic stability. The research method in this article uses qualitative methods, taking credible sources from various literature such as website articles, mass media, conference publications and scientific articles. This paper reveals that regardless of France’s domination in knowledge and funds, France is not the hegemonic power in the ESA. While an organization is normally featured with domination, this paper argues that power domination in the ESA is dynamically shared among the country members to accomplish a more collaborative rather than dominative feat. This leads to a a solid structure within the ESA and renders power-based domination irrelevant.